Supervision and In-Service Training as Correlates of Secondary School Teachers’ Productivity in Ogun East Senatorial District - Garuba, Qudus Ajibola; Omidiji, Ifeoluwa Abigael; Adeoye, Fatimah Jadesola (African Journal of Educational Management, 2024)
Secondary education is facing a lot of problems that has given rise to poor outputs or products. It was observed that poor quality of products from secondary schools was as a result of multi-faceted problems bedeviling the system in Nigeria. Such problems are inadequate facilities, low morale of teachers, poor supervision of schools, frequent changes in educational policies, lack of in-service training and so on. It is against this background problem that the study investigated the relationship among supervision, in-service training and secondary school teachers’ productivity in Ogun State East Senatorial District of Ogun State, Nigeria. This study adopted the descriptive research design of the survey type, while the simple random sampling technique was used to select the sample. The sample of the study were 500 respondents. The research instrument was tagged: Supervision, InService Training and Secondary School Teachers’ Productivity Questionnaire (SISTSSTPQ). The reliability co-efficient of the instrument was 0.77. Inferential statistics of Pearson Product Moment Correlation (PPMC) was used to test hypotheses 1-2 and hypotheses 3 was tested using Regression Analysis at p<0.05 level of significance. The result of the study showed that there was significant and positive relationship between supervision and secondary school teachers’ productivity, r = (0.724), (0.017), p<0.05; the hypothesis two revealed that there was significant and positive relationship between in-service training and secondary school teachers’ productivity, r = (0.765), (0.014), p<0.05; while the hypothesis three revealed that there was composite relationship among supervision, in-service training and secondary school teachers’ productivity; F(2, 480) = 36.943, P<0.05. The study concluded that supervision and in-service training has great implication on secondary school teachers’ productivity. It was therefore recommended that there should be constant full supervision in both government and private owned secondary schools on yearly basis. Government should provide opportunities for teachers to attend trainings regularly so as to keep them abreast of present global trends in teaching and learning process.